Faktor-Faktor yang Berhubungan dengan Kelelahan Kerja pada Pengendara Ojek Online di Jakarta Timur Tahun 2018 - Elwindra Elwindra; Muhammad Rizal (Jurnal Persada Husada Indonesia, 2019)
Fatigue is a condition that has a sign of reduced capacity that a person has for activities and is usually characterized by a feeling of fatigue and weakness. The purpose of this study was to determine the factors associated with work exhaustion on online motorcycle taxi drivers. The design of this study is an analytical study using a quantitative approach, with a cross sectional study, where the research subjects were Online Ojek Riders in East Jakarta with a sample of 80 respondents. The results showed that the highest BMI category measurement was in the Normal category 58.8%, while in the skinny-fat category 41.3%. The results of the study found that the condition of online motorcycle taxi drivers experienced mild fatigue as much as 75.0%. The results of Bivariate analysis p-value values ​​get a relationship between age variables (p-value: 0.210), marital status (p-value: 0.549), educational background (p-value: 0.131), working time (p-value: 0.447) , BMI (p-value: 0.605) with the variable exhaustion of online motorcycle taxi drivers. It can be concluded that there was no significant relationship between age with work fatigue, marital status with work exhaustion, educational background with work fatigue, work time with work exhaustion, BMI with work exhaustion. It is recommended for motorcycle taxi drivers online to add insight into good Safety Riding, so that it can reduce the risk of work fatigue.